Tool making, hand morphology and fossil hominins - Marzke, Mary W. (The Royal Society, 2013)
Was stone tool making a factor in the evolution of human hand morphology? Is it possible to find evidence in fossil hominin hands for this capability? These questions are being addressed with increasingly sophisticated studies that are testing two hypotheses; (i) that humans have unique patterns of grip and hand movement capabilities compatible with effective stone tool making and use of the tools and, if this is the case, (ii) that there exist unique patterns of morphology in human hands that are consistent with these capabilities. Comparative analyses of human stone tool behaviours and chimpanzee feeding behaviours have revealed a distinctive set of forceful pinch grips by humans that are effective in the control of stones by one hand during manufacture and use of the tools. Comparative dissections, kinematic analyses and biomechanical studies indicate that humans do have a unique pattern of muscle architecture and joint surface form and functions consistent with the derived capabilities. A major remaining challenge is to identify skeletal features that reflect the full morphological pattern, and therefore may serve as clues to fossil hominin manipulative capabilities. Hominin fossils are evaluated for evidence of patterns of derived human grip and stress-accommodation features.